Image transmission using visible light communication in data communication - Alfajri Tsaqifurrosyid; Mia Rosmiati; Moch. Fachru Rizal (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The development of network communication technology is currently developing rapidly, one of which is the use of LED lights that are not only used as lighting in the room but can also be used as a medium of data communication between users through light media. VLC is the latest innovation in the field of data communication that is currently being developed where the process of sending data used light media.. The simulation  of sending data using VLC can be done on the transmitter and receiver side by using Visual Studio application as an application that can visualize the process of sending data. By using this system the process of sending data every bit from transmiiter to the receiver can be seen so that the success rate of sending data can be easily seen by the user. system used arduino Uno as microprocessor. From the test results obtained the success rate of displaying images sent by the transmitter is 100% with a maximum distance of 50 cm with an image capacity of 20 KB with a delivery time of approximately 30 minutes.